STUDY OF WIND SPEED VARIABILITY AND THE DISTRIBUTION OF ABUNDANCE OF MOLECULES ON TITAN FROM ALMA'S OBSERVATIONS - Badingah, Luluatul
The atmosphere of Titan, Saturn's largest satellite, is an interesting object to study because it has similar complexity to Earth's atmosphere. The existen- ce of a general pole-to-pole one-cell circulation and hydrocarbon cycle suggests that Titan's atmosphere is highly dynamic. Wind observation is one of the main sources of information for studying the dynamics of Titan's atmosphe- re. Measuring the Doppler shift of molecular emission lines is one of several methods used to determine wind speed in Titan's atmosphere. HNC, HCN, HC3N, and CH3CN are few examples of molecules that can be used to probe wind speed because of their high abundance in dierent altitude regions, with their emission spectral peaks coming from 990, 745, 710, and 345 km, respec- tively. Wind speed measurements based on radio telescopes observations have been carried out in 2003, 2004, 2016, and 2017, which provide an evidence of the existing variability. In this thesis research, the author conducted a study of wind speed variability and molecules abundance distribution of HNC, HCN, HC3N, and CH3CN on Titan. To determine the value of wind speed in Titan's atmosphere, this research utilizes ALMA observation data in 2012, 2013, 2016, and 2017, data processing using CASA, and tting using Simple Linear Regres- sion (SLR). The results for each molecule show that the wind speed values in Titan's atmosphere increased from 2012 to 2016 and decreased in 2017. This result supports claim from previous observations that show an increase in wind speed towards 2016 and a decrease wind speed in 2017.